Identification of Protein Peptides by HPLC-Mass Spectrometry - Zhou, Chuanqi; Wang, Qingshuang (Asian Journal of Chemistry, 2010)
Fluid albumin as one important structure in egg was not focused on protein changes by scientists in the past years, especially effects by different breeding modes on laying hens. Through HPLCmass spectrometry method, protein peptides in fluid albumin could be identified. Free-cage (FC) and in-cage (IC) mode were performed in this study to breed the laying hens and the eggs were collected only after laying on one day. Through a rapid 1-dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis (1D-SDS PAGE), fluid albumin were separated and concentrated quikly. The uper-gel on SDS PAGE were cut and digested by trypsin. By nanoliquid chromatography coupled with mass spectrometry identification, 9 proteins were found, including 5 were in in-cage breeding mode and 4 were in free-cage breeding mode. However, 1 protein, lysozyme C, was celected as a new poteitial marker to distinguish the in-cage and freecage eggs.